Development of microsatellite markers for Thekopsora areolata, the causal agent of cherry spruce rust. Issue 3 (1st February 2018) - Capador, H.; Samils, B.; Olson, Å.
Summary: Cherry spruce rust is a fungal disease of Norway spruce cones caused by Thekopsora areolata and responsible for significant losses in seed production in Sweden and Finland. Here, we report the first set of nine microsatellites, which will allow an effective genetic fingerprinting of T. areolata . The markers were isolated using the FIASCO method and were characterized using DNA from 49 single aecia sampled from spruce cones in three different seed orchards in Sweden. Eight of the nine markers were shown to be polymorphic among the aecia. The markers were unlinked and are therefore suitable for future population genetic studies.